Some Properties of Complex Harmonic Mapping. (17th May 2012) - Eljamal, E. A.; Darus, M.
Abstract : We introduce new class of harmonic functions by using certain generalized differential operator of harmonic. Some results which generalize problems considered by many researchers are present. The main results are concerned with the starlikeness and convexity of certain class of harmonic functions.